Adsorption of basic rhodamine red, basic methylene blue, reactive procion red, and reactive procion blue textile dyes by cornstalk - Valencia, S. A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
The kinetics of the adsorption and equilibrium adsorption isotherms of four dyes - Basic Rhodamine Red (BRR), Basic Methylene Blue (BMB), Reactive Procion Red (RPR), and Reactive Procion Blue (RPB) - on cornstalk were investigated. The capacity of cornstalk to adsorb is high for basic dyes and low for reactive dyes. Within 12 h, the two basic dyes were reduced by about 75% in solution, the two reactive dyes only about 7%. The cornstalk adsorbed an average of 115.76 mg BRR, 111.50 mg BMB, 211.64 mg RPB, and 102.73 mg RPR per min. The pith had at least twice the adsorptive capacity of the skin. The maximum adsorptive capacities obtained for the two basic dyestuffs were high, i.e., 296.56 mg (pith), 156.27 mg (skin), and 180.38 mg (whole cornstalk) of BRR and 476.19 mg (pith), 285.71 mg (skin), and 333.33 mg (whole cornstalk) of BMB per gram.